2017
DOI: 10.3354/esr00838
|View full text |Cite
|
Sign up to set email alerts
|

Foraging areas, migratory movements and winter destinations of blue whales from the western North Atlantic

Abstract: The blue whale Balaenoptera musculus is a wide-ranging cetacean that can be found in all oceans. In the North Atlantic, little is known about blue whale distribution and genetic structure, or about the interconnections between areas of aggregations in Icelandic waters, the Azores, N orthwest Africa, and the N orthwest Atlantic. Seasonal movements and habitat use of blue whales, including the location of breeding and wintering areas, are also poorly understood. We used satellite telemetry to track movements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 86 publications
2
39
0
Order By: Relevance
“…Tracks or segments of tracks that were shorter than 3 transmitting days were removed. Priors for movement parameters were chosen based on previous studies 12,36,37,44,45 . Based on the resolution of the Argos derived location data, the hSSSM was fitted using a time step of 2 h (comprising 90% of time steps recorded and corresponding to the mean duration between locations).…”
Section: Methods Transmitter Deployments and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracks or segments of tracks that were shorter than 3 transmitting days were removed. Priors for movement parameters were chosen based on previous studies 12,36,37,44,45 . Based on the resolution of the Argos derived location data, the hSSSM was fitted using a time step of 2 h (comprising 90% of time steps recorded and corresponding to the mean duration between locations).…”
Section: Methods Transmitter Deployments and Data Collectionmentioning
confidence: 99%
“…Departure times from Svalbard for the fin whales were identified following Lesage et al 44 as a consecutive period of ≥ 48 h of hSSSM-predicted transiting behaviour (i.e. mean estimates < 1.25).…”
Section: Methods Transmitter Deployments and Data Collectionmentioning
confidence: 99%
“…In contrast, sperm whales (Physeter macrocephalus) were rarely detected at the equatorial Pacific seamount chain 11 and their seasonal presence at Kelvin seamount (~1600 m) appears to be related to regional variations in primary productivity 12 . Satellite telemetry studies showed that humpback whales (Megaptera novaeangliae) spent several days around the Antigonia seamount (60 m) and Torche Bank (30 m), off New Caledonia 13 , while North Atlantic blue whales (Balaenoptera musculus) occasionally engaged in area-restricted search (ARS) behaviours in the deep waters (>5000 m) around New England Seamounts 14 . In a similar study also based on satellite telemetry data, blue and fin (B. physalus) whales also engaged in ARS behaviour along a chain of shallow seamounts off the Azores 15 .…”
mentioning
confidence: 99%
“…The mother-calf pairs of blue whales observed off northeastern Brazil (de Oliveira 2015) (Fig. 1) were close to the shelf break, and in the vicinity of deep ocean structures, a suitable environment for the euphausiid aggregation (Genin 2004;Lesage et al 2017). Mother-calf pairs of humpback whales have been recorded along the Potiguar basin (de Oliveira 2015) and the waters off northeastern Brazil have been considered a breeding ground for minke whales (Andriolo et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Blue whale populations in the Southern Hemisphere were depleted by commercial whaling (IWC (International Whaling Commission) 2006) and their numbers have yet to recover (Branch et al 2004;Branch et al 2007). Furthermore, the species tends to inhabit deep offshore waters during the breeding season (Double et al 2014;Torres-Florez et al 2015;Lesage et al 2017;Hucke-Gaete et al 2018) and the limited cetacean-oriented survey efforts in deep waters of the western South Atlantic (e.g. Di Tullio et al 2016) translates in few chances of blue whale encounters.…”
Section: Discussionmentioning
confidence: 99%